Synthesis and characterization of zinc oxide nanopowder; Inorganic and Nano-Metal Chemistry; Vol. 51, iss. 6 - Zhuravlev M. V. Mikhail Valerievich; Sazonov R. V. Roman Vladimirovich; Kholodnaya G. E. Galina Evgenievna; Pyatkov I. Igor; Ponomarev D. V. Denis Vladimirovich; Konusov F. V. Fedor Valerievich; Lapteva O. P. Olga Pavlovna; Gadirov R. M. Ruslan Mukhamedzhanovich (2021, 2021)
Title screen